Dietary quality and nutrition: Past progress, current and future challenges - Mahrt, Kristi; Headey, Derek D.; Ecker, Olivier; Comstock, Andrew R.; Tauseef, Salauddin (International Food Policy Research Institute, 2024)
Prior to the onset of the COVID-19 pandemic in 2020 and the military coup in 2021, Myanmar was experiencing a period of rapid economic growth and transformation in the wake of economic and political liberalization. Between 2005 and 2017, average annual growth in real GDP per capita was 7.8 percent, making Myanmar the fastest growing economy among the Association of Southeast Asian Nations (ASEAN) countries. Strong growth was accompanied by a halving of the national poverty rate between 2005 and 2017 from 48.2 to 24.8 percent (CSO, UNDP, and World Bank 2019). COVID19 and the economic and political shocks affecting the country since 2021 have led to an economic contraction: 2021 saw an 18 percent drop in real GDP per capita; in 2022, real GDP per capita was estimated to be 15 percent lower than in 2019 (World Bank 2022). The impacts on poverty were even more dire. A high-frequency panel phone survey of mothers and young children in urban Yangon and the rural Dry Zone revealed incomes collapsing during the COVID-19 lockdowns and further income losses in the wake of the February 2021 military takeover (Headey et al. 2022). Prices rose dramatically, with the consumer price index rising by 20 percent between July 2021 and July 2022 (MOPF 2022), while food prices rose by 34 percent over the same period and by about 50 percent between December 2021 and December 2022. Nationally, a variety of different poverty indicators suggest that between 40 and 50 percent of the population was living in poverty in 2022 —poverty rates similar to those found between 2005 and 2010.